(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The main content of the article is to improve the methodology of teaching biology on the basis of a competency-based approach and the use of modern pedagogical technologies and opportunities for biology teachers to use modern pedagogical technologies in general secondary schools, a competency approach in general secondary schools The basis is the development of pedagogy and psychology in improving the methods of teaching biology.